The Association Between Prosocialness, Relational-Interdependent Self-construal and Gender in Relation to Burnout Among Swedish Clergy - Buratti, Sandra (Rev Relig Res, 2020)
Serving as a clergyperson is a highly variable profession and in recent decades, the role has evolved and expanded even further. Consequently, the demands have increased and with it the risk for stress-related ill-health and absenteeism. The aim of the current study was to evaluate, in a larger sample of Swedish clergy (N = 871), two possible antecedents of burnout, namely prosocialness and relational-interdependent self-construal. A further aim was to explore potential gender differences in the investigated associations. The direct and indirect relationships of prosocialness and relational-interdependent self-construal to two dimensions of burnout, exhaustion, and disengagement were investigated in a structural equation-modelling framework. The results showed that clergy who reported higher prosocialness experienced more stress in their work, in terms of both quantitative and emotional demands, which in turn was associated with higher levels of exhaustion and disengagement. But prosocialness was also found to be directly associated with lower levels of disengagement, as well as indirectly associated with higher levels of role clarity. However, no direct or indirect associations were found between relational-interdependent self-construal and any dimension of burnout. Regarding gender differences, female clergy reported higher levels of prosocialness and job demands, less role clarity, and in turn more exhaustion compared to male clergy. This indicated a more stressful situation for female clergy. Our study contributes new insights into the role that personality plays in different dimensions of burnout in clergy, as well as insights into an understanding of gender differences in burnout among clergy.